Post-myocardial infarction ventricular septal defects: incidence and treatment trends during and after the COVID-19 pandemic - Giuseppe Nasso; Ignazio Condello; Walter Vignaroli; Andrea Antonazzo; Francesco Bartolomucci; Barbara Pala; Claudio Larosa; Annachiara Pingitore; Vincenzo Amodeo; Vincenzo Montemurro; Mizar D’Abramo; Roberto Ceravolo; et al. (Scientific Reports)
Abstract Ventricular septal defect (VSD) is a serious complication of myocardial infarction (MI), with its global incidence significantly reduced in recent years due to advances in coronary reperfusion techniques. However, during the COVID-19 pandemic, there was an unexpected rise in the incidence of post-MI VSD, likely driven by delays in seeking treatment. This study retrospectively analyzed 10 cases of post-MI VSD treated at our hospitals from March 2018 to August 2023, comparing incidence rates across pre-pandemic, pandemic, and post-pandemic periods. The findings revealed a notable increase in VSD cases during the pandemic, with six cases occurring in two years, compared to only two cases in each of the pre-pandemic and post-pandemic periods. Despite these fluctuations, surgical intervention remained a crucial and effective treatment, with 60% of patients surviving the 30-day follow-up. The study underscores the impact of delayed treatment on VSD incidence during the pandemic and highlights the critical need for timely medical intervention to manage severe MI complications effectively.